Chart of Smith Strait - Kane, Elisha Kent, 1820-1857 (1852)
E.K. Kane's map 1852-55" -- handwritten note in bottom margin. "Evidently prepared under the direction of E.K. Kane. In comparing it with a map in "Arctic explorations in the years 1853, '54, '55" by Elisha Kent Kane, Vol. 1, 1856, it will be noted that, with one or two exceptions, the location of the place names correspond almost exactly." -- note pasted on. Color;